2016
DOI: 10.2139/ssrn.2740988
|View full text |Cite
|
Sign up to set email alerts
|

Public Debt and Economic Growth Economic Systems Matter

Abstract: Most studies on the relationship between public debt and economic growth implicitly assume homogeneous debt effects across their samples. We -in accordance with recent literature-challenge this view and state that there likely is a great deal of cross-country heterogeneity in that relationship. However, other than scholars assuming that all countries are different, we expect that clusters of countries differ. We identify three country clusters with distinct economic systems: Liberal (Anglo Saxon), Continental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Apart from studies that have found nonlinear impact of public debt on economic growth, there is a large body of empirical work that supports a negative impact between these two variables. These studies include Gómez-Puig and Sosvilla-Rivero (2015; 2017), Ahlborn and Schweickert (2016), Panizza and Presbitero (2013), Szabo (2013), Égert (2012), Afonso and Jalles (2011), Cochrane (2011a, 2011b), Kumar and Woo (2010), the International Monetary Fund (2005), and Clements, Bhattacharya, and Nguyen (2003).…”
Section: The Empirical Arguments On the Impact Of Public Debt On Econmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from studies that have found nonlinear impact of public debt on economic growth, there is a large body of empirical work that supports a negative impact between these two variables. These studies include Gómez-Puig and Sosvilla-Rivero (2015; 2017), Ahlborn and Schweickert (2016), Panizza and Presbitero (2013), Szabo (2013), Égert (2012), Afonso and Jalles (2011), Cochrane (2011a, 2011b), Kumar and Woo (2010), the International Monetary Fund (2005), and Clements, Bhattacharya, and Nguyen (2003).…”
Section: The Empirical Arguments On the Impact Of Public Debt On Econmentioning
confidence: 99%
“…Ahlborn and Schweickert (2016), while testing the relationship between public debt and GDP growth using a sample of 111 OECD and developing countries for eight 5-year periods from 1970 to 2010, concluded that the link between public debt and GDP growth varies considerably across countries due to the degree of fiscal uncertainty brought about by each economic system. After employing varying methodologies, which include time-fixed effects, random effects pooled ordinary least squares (OLS), and two-stage least squares, the empirical findings of Ahlborn and Schweickert (2016) suggest that public debt has a strong negative impact on GDP growth in continental countries than in liberal countries.…”
Section: The Empirical Arguments On the Impact Of Public Debt On Econmentioning
confidence: 99%
“…While a considerable body of past investigation on the subject proposes a negative connection between public debt and economic growth (Abbas & Christensen, 2010;Ahlborn & Schweickert, 2016;Akram, 2015Akram, , 2016Al Kharusi & Ada, 2018;Clements, Bhattacharya, & Nguyen, 2003;Egert, 2015;Gomez-Puig & Sosvilla-Rivero, 2018;Hansen, 2002;Huang, Panizza, & Varghese, 2018;Kumar & Woo, 2010;Mhlaba & Phiri, 2019;Panizza & Presbitero, 2014;Reinhart & Rogoff, 2010a;Reinhart & Rogoff, 2010b;Sachs, 1989;Schclarek, 2004;Serieux & Yiagadeesen, 2001;Szabo, 2013;Weeks, 2000;Woo & Kumar, 2015), two conflicting viewpoints still subsist.…”
Section: Introductionmentioning
confidence: 99%
“…The empirical literature on the symmetric impact of public debt on economic growth is extensive and has been rising over time. The findings vary depending on the estimation modelling technique utilised, model specification, and the time frame considered, among other variables (see, for example, Saungweme, Odhiambo, 2021; Gómez-Puig, Sosvilla-Rivero, 2018; Ahlborn, Schweickert, 2016). There is also an ample body of literature that support the nonlinear relationship between public debt and economic growth.…”
Section: Introductionmentioning
confidence: 99%